2010
DOI: 10.1111/j.1742-481x.2010.00706.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence on pressure transduction when using different drainage techniques and wound fillers (foam and gauze) for negative pressure wound therapy

Abstract: Pressure transduction to the wound bed in negative pressure wound therapy (NPWT) is crucial in stimulating the biological effects ultimately resulting in wound healing. In clinical practice, either foam or gauze is used as wound filler. Furthermore, two different drainage techniques are frequently employed. One involves the connection of a non-perforated drainage tube to the top of the dressing, while the other involves the insertion of perforated drains into the dressing. The aim of this study was to examine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…In addition to comparing two systems of NPWT, the results of this study may also add insight into the role of foam and gauze and their relative effectiveness with NPWT. These data support, for at least a subset of chronic wounds, similar efficacy for both foam and gauze interfaces, and this is consistent with some published studies . However, the specific wound types that may respond best to each form of wound interface layer during NPWT still need to be defined further clinically in additional studies.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In addition to comparing two systems of NPWT, the results of this study may also add insight into the role of foam and gauze and their relative effectiveness with NPWT. These data support, for at least a subset of chronic wounds, similar efficacy for both foam and gauze interfaces, and this is consistent with some published studies . However, the specific wound types that may respond best to each form of wound interface layer during NPWT still need to be defined further clinically in additional studies.…”
Section: Discussionsupporting
confidence: 87%
“…These data support, for at least a subset of chronic wounds, similar effi- cacy for both foam and gauze interfaces, and this is consistent with some published studies. [24][25][26][27] However, the specific wound types that may respond best to each form of wound interface layer during NPWT still need to be defined further clinically in additional studies. It may be entirely plausible foam interfaces may perform better in deeper wounds with exposed structures than gauze interfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Most NPWT publications relate to the use of polyurethane open cell foam (V.A.C., Kinetic Concepts Inc., San Antonio, TX), rather than the gauze dressing we used. For this discussion, we have made the assumption that the mechanisms of action are similar for both types of contact dressing, based on recent studies showing equally effective delivery of negative pressure and deformation with either type . The widely reported successes of NPWT are probably because of mechanisms of action that have been proven with in vivo and in vitro studies.…”
Section: Discussionmentioning
confidence: 99%
“…The efficiency of pressure transduction to the wound from the vacuum pump depends on the structure or nature of the wound filler. In previous studies, authors have shown that interface dressings influence the delivery of negative pressure (17). However, a recent report confirmed that the type of wound filler (foam or gauze) does not affect the pressure transduction to the wound bed and they could provide similar pressure transduction to the wound bed (18).…”
Section: Discussionmentioning
confidence: 98%